2023
DOI: 10.1101/2023.01.08.523155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early life experience with natural odors modifies olfactory behavior through an associative process

Abstract: Past work has shown that chronic exposure of Drosophila to intense monomolecular odors in early life leads to homeostatic adaptation of olfactory neural responses and behavioral habituation to the familiar odor. Here, we found that, in contrast, persistent exposure to natural odors in early life increases behavioral attraction selectively to familiar odors. Odor experience increases the attractiveness of natural odors that are innately attractive and decreases the aversiveness of natural odors that are innatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
2
1
0
Order By: Relevance
“…In one study where flies were chronically exposed to monomolecular odors at lower concentrations (~0.01–1%) that are attractive to flies, odor experience increased behavioral attraction toward the familiar odor ( Chakraborty et al, 2009 ). In agreement, other work from our laboratory shows that chronic exposure of flies in early life to odors from natural sources increases behavioral attraction to these odors ( Dylla et al, 2023 ). These observations argue against habituation being the dominant effect of chronic odor exposure on behavior since, if that were the case, reduced attraction to familiar attractive odors is expected.…”
Section: Discussionsupporting
confidence: 91%
“…In one study where flies were chronically exposed to monomolecular odors at lower concentrations (~0.01–1%) that are attractive to flies, odor experience increased behavioral attraction toward the familiar odor ( Chakraborty et al, 2009 ). In agreement, other work from our laboratory shows that chronic exposure of flies in early life to odors from natural sources increases behavioral attraction to these odors ( Dylla et al, 2023 ). These observations argue against habituation being the dominant effect of chronic odor exposure on behavior since, if that were the case, reduced attraction to familiar attractive odors is expected.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings contradict some earlier results that either showed a general decrease (Das et al, 2011;McCann et al, 2011;Sachse et al, 2007;Sudhakaran et al, 2013) or an increase (Kidd & Lieber, 2016;Kidd et al, 2015) of PN signaling after long-term odor exposure. The consistency of the neuronal signals we observed within the circuit indicates that physiological changes downstream of PNs may be responsible for the behavioral effects, as also suggested by two recent studies (Dylla et al, 2023;Gugel et al, 2023) that obtained similar physiological results. It is conceivable that glomerulus-or odor-specific mechanisms cause the different physiological effects observed across studies.…”
Section: Long-term Exposure To Geosmin Elicits Behavioral Changessupporting
confidence: 87%
“…Although some previous studies demonstrated that long-term exposure of odorants causes behavioral changes in flies (Chodankar et al, 2020;Devaud et al, 2001;Devaud et al, 2003;McCann et al, 2011;Sachse et al, 2007;Sudhakaran et al, 2013), it was never shown that such changes can also be induced by a highly specific and unambiguous odorant like geosmin. Our T-maze and oviposition experiments demonstrated that female flies previously exposed to geosmin were subsequently less repelled by this odorant, likely due to an associative learning process (Dylla et al, 2023). This challenges the postulated predictability in the behavioral outcome of "labeled line" signaling in the olfactory system (Keesey & Hansson, 2021).…”
Section: Long-term Exposure To Geosmin Elicits Behavioral Changesmentioning
confidence: 68%